The Frequency of Infectious Diseases and Usage of Antibiotics in Admissions to Yenimahalle and Abdullahpaşa Education and Research Health Center in 2000 - Ozan, Ahmet Tevfik; Açık, Yasemin; Oğuzöncül, A. Ferdane; Polat, S. Aytaç; Deveci, S. Erhan (Fırat University, 2002)
Aim: The aim of this study is determining the frequency of infectious diseases and evaluating generaly usage of antibiotics in infectious diseases in policlinic admissions to Yenimahalle and Abdullahpaşa Education and Research Health Center (ERHC) in 2000. Material and Methods: The data about distrubition of infectious diseases and usage of antibiotics were investigated retrospectively from policlinic records of Health Centers between 1 January-31 December 2000. Results: The rates of cases who were diagnosed infectious diseases in all policlinic applications were 45.7% in Yenimahalle, 49.0% in Abdullahpaşa. Acute respiratory tract infectious took first place between infectious diseases (28.2%, 25.7% respectively), and urinary tract infectious followed it (4.2%, 4.0% respectively) in Yenimahalle and Abdullahpaşa Health Centers. Lower respiratory tract infectious were the most commonly seen diseases in both health center between all ages. In Yenimahalle Health Center 24.8% and in Abdullahpaşa Health Center 23.0% the patients with infectious diseases were not given antibiotics. In Yenimahalle ERCH, ampicillin and sulbactam combination (15.1%) and in Abdullahpaşa ERCH, penicillin (20.1%) took first place in all antibiotics groups. Conclusion: The admissions of infectious disease are common in first step. Necessary studies must be made for prevention, control and working right of treatment service of the infectious diseases.

Amaç: Bu araştırma, 2000 yılında Yenimahalle ve Abdullahpaşa Eğitim Araştırma Sağlık Ocaklarına (EASO) yapılan poliklinik başvuruları içerisinde enfeksiyon hastalıkları sıklığını belirlemek ve enfeksiyon hastalıklarında antibiyotik kullanımının genel olarak değerlendirilmesi amacıyla yapılmıştır. Gereç ve Yöntem: Sağlık ocaklarının (SO) 1 Ocak-31 Aralık 2000 tarihleri arasındaki poliklinik kayıtlarından, enfeksiyon hastalıklarının ve kullanılan antibiyotiklerin dağılımları ile ilgili veriler retrospektif olarak incelenmiştir. Bulgular: Toplam poliklinik başvuruları içerisinde enfeksiyon hastalığı tanısı alan kişi oranı Yenimahalle EASO'da %45.7, Abdullahpaşa EASO'da %49.0'dır. Yenimahalle ve Abdullahpaşa EASO'larında enfeksiyon hastalıkları arasında ilk sırayı akut solunum yolu enfeksiyonları (ASYE) almakta (%28.2, %25.7), bunu idrar yolları enfeksiyonları (İYE) izlemektedir (%4.2, %4.0). Her iki SO'da da ASYE tüm yaş gruplarında en fazla görülen enfeksiyon hastalığıdır. Yenimahalle EASO'da enfeksiyon hastalıklarının %24.8'ine, Abdullahpaşa EASO'da ise %23.0'ına antibiyotik verilmemiştir. Yenimahalle'de reçetelenen antibiyotik grupları içerisinde ilk sırayı ampisilin ve sulbaktam kombinasyonu (%15.1), Abdullahpaşa'da ise penisilin grubu (%20.1) almaktadır. Sonuç: Birinci basamakta enfeksiyon hastalığı başvuruları oldukça yoğundur. Enfeksiyon hastalıklarına yönelik koruyucu, denetleyici ve tedavi edici hizmetlerin aksamaması için gerekli çalışmalar yapılmalıdır.
2000 YILINDA YENİMAHALLE ve ABDULAHPAŞA EĞİTİM ARAŞTIRMA SAĞLIK OCAKLARINA YAPILAN BAŞVURULARDA ENFEKSİYON HASTALIKLARI SIKLIĞI ve ANTİBİYOTİK KULLANIMI